PENGEMBANGAN E-LKPD DENGAN PENDEKATAN DEEP LEARNING PADA MATERI STATISTIKA KELAS X SMA NEGERI 5 GORONTALO - Nurmin A. Hunalo; Evi Hulukati; Khardiyawan A. Y. Pauweni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce an Electronic Student Worksheet (E-LKPD) utilizing a Deep Learning approach for the statistics unit in Grade X at SMA Negeri 5 Gorontalo, ensuring it meets validity and practicality criteria. The study is motivated by students' low mathematical thinking skills and a lack of interactive teaching materials capable of visualizing statistical concepts in a contextual manner, which hinders students' understanding of the subject matter. The research employs the Research and Development (R&D) method, specifically the 4D development model, which comprises four main stages: Define, Design, Develop, and Disseminate. Data collection instruments included validation questionnaires for media and subject matter experts, as well as student and teacher response questionnaires to assess the product's practicality. The trial subjects were Grade X students at SMA Negeri 5 Gorontalo. The results indicate that the Deep Learning-based E-LKPD met the validity criteria according to expert evaluators, following recommended adjustments to content and layout. Assessments of practicality based on user/student and teacher response questionnaires also yielded positive results, categorizing the material as